Suitability of Blockchain for Storing Private Data from IoT Devices - Marija Cekuš; János Simon (Interdisciplinary Description of Complex Systems)
The explosive growth of Internet of Things devices over the past two decades has created pressing challenges for storing the vast amounts of data generated by connected devices. Concurrently, blockchain technology has rapidly evolved, providing new avenues for storing data securely, efficiently, and in near real-time. This article investigates the suitability of various blockchain platforms for Internet of Things data storage, selecting seven platforms – namely, IOTA, Signum, Ethereum, Solana, Polygon, Stellar, and Hyperledger Sawtooth. A comprehensive set of criteria and scoring methodology were developed to assess each platform’s strengths and limitations for this use case.